PENGEMBANGAN LEMBAR KERJA SISWA (LKS) DENGAN TAMPILAN MAJALAH PADA MATERI SISTEM REPRODUKSI MANUSIA UNTUK SISWA SMA - Septiyani, Ira - (Pendidikan Biologi, 2014)
Based on researcher sight for doing Practice Field (PL) and the result of interview by one of the biology teacher in SMA Pertiwi 2 Padang is gotten information that in learning process for material which is teacher used like book, and student is too few who has book. The material which is used for the picture is not clear enough and the color is not bright, so that itâs need the developing student work sheet (LKS) with magazine view. This research purpose to produce LKS with magazine view for human reproduction system for SMA and also know validity and practicality. This research is development research which is used 4-D Model with 4 levels, define (define), design (design), develop (develop), and disseminate (disseminate). The define level is consist of front analysis, student analysis, task analysis, and concept analysis. In design level is done the material like LKS by magazine view in human reproduction system material. The develop level is done by validity test by validation who is consist of 2 lectures STKIP PGRI West Sumatra and 1 teacher from SMA Pertiwi 2 Padang. Practicality test by 1 teacher and 29 students of class XII IPA. In disseminate level is not done. Itâs until develop level. In this data research is premier data which is gotten from questionnaire validity and practicality, then itâs analyzed by statistic descriptive. The result of LKS validity by magazine from validation show that this LKS in valid criteria is 85,55% and the practicality result of LKS by the teacher with the mark 94,44% as average categorized as practice and student with average 89,01% categorized as very practice. It can be concluded that LKS with the magazine view in human reproduction system which is produced has completed valid criteria and very practice.